Psychiatric morbidity after screening for breast cancer. Issue 1 (March 1986) - Dean, C; Roberts, M M; French, K; Robinson, S
Abstract : One hundred and thirty two women with normal breast screening results were interviewed six months after their attendance at the Edinburgh Breast Screening Clinic. Eight percent of women said screening had made them more anxious about developing breast cancer. Thirty eight percent said they were more aware of the disease since screening but they regarded this as advantageous. Seventy percent of the women were still practising breast self-examination. There was no difference in the psychiatric morbidity of the screened sample when compared with a matched random sample community control group. Neither was there any difference in the General Health Questionnaire case rates before and after screening. Screening does not appear to increase the prevalence of psychiatric morbidity. Twenty nine percent of the interview sample were examining their breasts more than once a month–21% once a week or more. However, these frequent self-examiners did not have a greater prevalence of psychiatric morbidity than their matched controls.